(untitled) (International Journal of Food and Nutritional Sciences, 2022)
For the production of crops, India has a broad agricultural sector. The best indicator of the health of farming is technical efficiency, which helps to maintain high levels of agricultural production. Aigner et al. (1977) and Meeusen and van den Broeck (1988) proposed stochastic frontier analysis (SFA), which is being used to evaluate a reliable measure of technical efficiency (1977). The advanced stochastic frontier analysis method developed by Colombi et al. (2014), Kumbhakar, Lien, and Hardaker (2014), and Tsionas and Kumbhakar (2014) is used in the current work. This method includes four error components and a multistage estimation procedure. The data was extracted from the Ministry of Agriculture and Farmers’ Welfare’s Comprehensive Cost of Cultivation Scheme (CCCS) for the period 2004–2019. The study will focus on four important crops: paddy, wheat, sugarcane, and maize. The study’s conclusion is that short- and long-term errors at decision-making units result in differences in transient technical efficiency and persistent technical efficiency for each crop (DMU).